Machine Learning Algorithms in Big data Analytics - Sree Divya, K; Bhargavi, P; Jyothi, S (International Journal of Computer Sciences and Engineering, 2025)
Big data is a wonderful supply of information and knowledge from the systems to other end-users. However handling such quantity of knowledge needs automation, and this leads to a trend of data processing and machine learning techniques. Within the ICT sector, as in several different sectors of analysis and trade, platforms and tools are being served and developed to assist professionals to treat their knowledge and learn from it automatically. Most of these platforms return from huge firms like Google or Microsoft, or from incubators at the Apache Foundation. This review explains Machine learning Algorithms in Big data Analytics, and machine learning challenges us to take decisions where there is no known “right path” for the specific problem based on previous lessons and enumerates some of the foremost used tools for analyzing and modeling big-data.